The Best Route to Take. - Gager, Susie (Policy & Practice (19426828), 2016)
The article highlights the system migration approach by the Colorado Department of Human Services (CDHS) to transform its Automated Child Support Enforcement System (ACSES) from Natural to Java and ADABAS software to a relational database management system. A background is provided on ACSES and how it was hindering the strategic goals of the CDHS. It outlines the procedure for the migration led by a team of software developers that was done with automation technology.